HUMAN RESOURCES DEVELOPMENT IN INCREASING COMPANY DEVELOPMENT (CASE STUDY PT. PARS MAXY PERKASA) - Slamet Heri Winarno; Lela Elvira; Jeffry Latumahina; Sabil Sabil; RR Roosita Cindrakasih; Arman Syah Putra (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to determine the variables that can affect the development of the company. The variables raised in this research are variables related to human resources. What things affect human resources will be discussed today so that it can be seen what things are which can affect the future development of the company. The problem raised in this study is how to determine the variables that can affect a company's development. Therefore, with the existing problems, it will be known how to improve the company in the future so that it can become a developing and advanced company so that the variables are known to be repaired. The method used in this study using two methods, namely the first method using a literature review and the second method is to use a quantitative method that will conduct a survey of 100 employees at a company PT. PARS MAXY PERKASA. The purpose of this study is how to find out the variables that can affect the development of the company. The variables raised in this study are the human resources variable and the company development variable. With these variables, the city of these variables can influence each other significantly, because the value of R Square is greater. Than 0.05 can be ascertained from human resources affect the development of the company